Checklist of the infraorder Gryllidea (Orthoptera: Ensifera) from Yunnan province, China, with description of one new species - Yuan, Li-Lan; Xu, Fei; Wang, Xiao-Xiao; Zhang, Dong-Xiao; Xie, Guang-Lin; Liu, Hao-Yu (Zootaxa, 2021)
A checklist of 166 species and subspecies from 62 genera, 15 subfamilies, 5 families and 2 superfamilies of Gryllidea, is recorded from Yunnan Province of China, based on the published data and accumulated material. The detailed distribution of most species is provided in Yunnan Province. Mitius eryuanensis Yuan, Xie & Liu sp. nov. is described as new species.